Teaching string technique through culturally diverse music - Plymell, Shannon (Kansas State University, 2023)
Utilizing culturally diverse folk songs in the orchestra classroom as a supplement to popularly used method books cultivates a positive environment for student learning and can also be used to teach a broad spectrum of technical skills. I taught the students the folk song A la rorro niño, a Mexican folk song as notated by Beth Thompson on her blog bethsnotesplus.com (2020). Through correspondence with Thompson, I learned that she had collected this song from her mother-in-law aurally. I have also used Karen Howard’s book First Steps in Global Music (2020) to find more information about this song. During my lessons we briefly discussed the history of the song, then used it to practice slur versus staccato articulations with my fifth grade beginning students and shifting and vibrato with my eighth grade students. In both classes the lesson was designed to support the advancement of performance technique while also including and uplifting a staple of the Mexican folk song tradition. I always knew my approach to teaching string students would include a strong set-up routine. The set-up and performance technique for string players is vital to preserving the joy in making music, preventing injuries commonly suffered by long-term string players, and also providing the groundwork for learning more advanced techniques as they grow as musicians and string players. Within some of my initial coursework in this Masters’ program, my professors affirmed this instinct and provided the structure and tools to explore and develop this passion. I also hold a strong belief that music education should serve as a vessel for broadening cultural awareness. Music exists in a unique cultural niche, as it is an international language and simultaneously an art form that can represent a fraction of society. This Masters’ program has guided my ability to incorporate this belief into the orchestra classroom. Within my project I utilized a Mexican folk song to teach performance techniques that reinforce a proper set-up for holding and playing their instruments with the intention of creating comfortable, joyous string players.
Keywords: String pedagogy; Orchestra; Folk music; Diverse representation; String technique